2020
DOI: 10.1177/0269881120914223
|View full text |Cite
|
Sign up to set email alerts
|

Acute mitragynine administration suppresses cortical oscillatory power and systems theta coherence in rats

Abstract: Background: Mitragynine is the major alkaloid of Mitragyna speciosa (kratom) with potential as a therapeutic in pain management and in depression. There has been debate over the potential side effects of the drug including addiction risk and cognitive decline. Aims: To evaluate the effects of mitragynine on neurophysiological systems function in the prefrontal cortex (PFC), cingulate cortex (Cg), orbitofro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…At the doses employed in the present study, animals showed no adverse effects with acute or repeated administration. We have previously characterized isolated mitragynine effects (10 mg/kg i.p., a standard dose used in the literature (Foss et al, 2020;Japarin et al, 2021;Suhaimi et al, 2021)) on neuronal oscillatory activity where we showed moderate frequency-specific changes in cortical regions only (Thériault et al, 2020). Further, our preliminary behavioural findings showed no effects of the same 10 mg/kg dose of mitragynine on behavioural responses in the tail-flick test (Supplementary Figure S1).…”
Section: Drugssupporting
confidence: 53%
See 2 more Smart Citations
“…At the doses employed in the present study, animals showed no adverse effects with acute or repeated administration. We have previously characterized isolated mitragynine effects (10 mg/kg i.p., a standard dose used in the literature (Foss et al, 2020;Japarin et al, 2021;Suhaimi et al, 2021)) on neuronal oscillatory activity where we showed moderate frequency-specific changes in cortical regions only (Thériault et al, 2020). Further, our preliminary behavioural findings showed no effects of the same 10 mg/kg dose of mitragynine on behavioural responses in the tail-flick test (Supplementary Figure S1).…”
Section: Drugssupporting
confidence: 53%
“…Specifically, whereas the extract from Cheaha et al (2015) was enriched with mitragynine, the extract used herein showed significant levels of other alkaloids, two of which that were in greater abundance than mitragynine. Indeed, we have previously shown that synthetic mitragynine has no effects on NAc oscillations ( Thériault et al, 2020 ). Differences in the composition of the extract are also exemplified by the dose used, with their dose as much as 160 times higher than the one used in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data may be supported by the findings of a recent study that showed LKT to induce fewer side effects (e.g., physical dependence/respiratory depression) compared to MOR without affecting motor activity (Wilson et al., 2020 ). Similarly, some authors reported that mitragynine is a compound with a minor addictive potential (Meepong and Sooksawate, 2019 ; Thériault et al., 2020 ; Yue et al., 2018 ), when compared to MOR (Cheaha et al., 2017 ; Harun et al., 2015 ), neither it caused physiological dependence (Harun et al., 2020 ). Moreover, despite kratom and 7HMG were reported to have rewarding effects (Gutridge et al., 2020 ), with 7HMG having a higher abuse potential (Hassan et al., 2019 ; Sabetghadam et al., 2013 ; Yusoff et al., 2016 ), a recent study found that both mitragynine and 7HMG did not show rewarding actions in the intracranial self‐stimulation (Behnood‐Rod et al., 2020 ).…”
Section: Discussionmentioning
confidence: 92%
“…Goh et al, 2014;Zailan et al, 2019;Rahman et al, 2022;Priatna et al, 2023 Table S2: The alkaloids and the scientific studies to evaluate their pharmacological activities. Carpenter et al, 2016, Matsumoto et al, 1996Thongpradichote et al, 1998;Hiranita et al, 2019;Foss et al, 2020;Shamima et al, 2012;Idayu et al, 2011;Meepong & Sooksawate, 2019;Fakurazi et al, 2013;Japarin et al, 2021;Gutridge et al, 2020;Apryani et al, 2010;Aznal et al, 2022;Iman et al, 2021;Suhaimi et al, 2021;Hassan et al, 2019;Behnood-Rod et al, 2020;Tsuchiya et al, 2002;Goh et al, 2014;Domnic et al, 2021;Priatna et al, 2023;Limcharoen et al, 2022;Aziz et al, 2022;Macko et al, 1972;Henningfield et al, 2022;Chittrakarn et al, 2010;Thériault et al, 2020;Jamil et al, 2013;Tohda et al, 1997;Obeng et al, 2019;Matsumoto et al,1997;León et al, Matsumoto et al, 2004;Matsumoto et al, 2005;Gutridge et al, 2020;Behnood-Rod et al, 2020;…”
mentioning
confidence: 99%